Addressing racism in housing access through public deliberation. A case study - Brugué, Quim; Carrera Fossas, Eduard; Shaimi, Mostafa; Tarragó, Daniel (Revista del CLAD Reforma y Democracia, 2025)
This article addresses a complex issue: racial discrimination in access to housing. It provides a normative and conceptual approach to the right to non-discrimination, focusing on Olot, Girona, where a public policy was designed to combat racism in the housing market. The study combines academic analysis of a growing problem with a knowledge transfer effort, structured through the management of a deliberative process to build this policy. Key findings include racial and cultural barriers limiting access to housing and the benefits and limitations of the deliberative approach to addressing these inequalities. Effective implementation requires commitment from local authorities. The article offers both theoretical and practical contributions, linking this issue to the debate on the deliberative turn in public policy.
Keywords: racism; housing policy; public deliberation; case study